China’s tactics in resisting the acceptance of civil and political human rights: how has China’s appeasement response towards the UN international human rights system challenged the universality of human rights norms - Vilakazi, Nobukhosi (My University, 2020)
Mainland China’s actions with respect to civil and political human rights have stirred pressure by the international community for China to approve and conform to the mentioned human rights norms by ratifying the ICCPR. However, Beijing’s response has been tactical not only to appease and quiet the pressure; it has also challenged the power of the socialisation and universality of human rights norms and standards. The introduction of the five-stage spiral model of human rights helps in revealing China’s preemptive behaviour and position in this regard, particularly in the third stage of tactical concession. China’s strategy of the use of appeasement as a human rights foreign policy tactic is to avoid the practice of civil and political human rights within the country, and also has been fueled by its status and power in global platforms such as the UN. China’s sovereignty has easily allowed the country to demean universal norms which threaten the country’s communist values. Moreover, China’s stubbornness to fully comply to human rights norms has further raised concerns with the efficiency of international humanitarian law in safeguarding human dignity. As China has not ratified the ICCPR, it leads to the questioning of the power of humanitarian law in socialising human rights norms to all UN member states. Nonetheless, Beijing’s influence in the expansion, or lack thereof, of human rights norms has challenged the universalism of the rights mentioned
A thesis submitted in partial fulfillment of the requirements of the degree Masters of Arts in International Relations, Faculty of Humanities, University of Witwatersrand September, 2020